P57kip2 Immunohistochemical Marker as a Diagnostic tool for Cases of Hydatidiform Moles in a Tertiary Health Facility in Southwestern Nigeria (2020)
Background: Hydatidiform mole (HM) is the most common gestational trophoblastic disease. P57kip2 has been reported to be helpful in differentiating between partial and complete HMs. Objectives: The study aims to evaluate the P57kip2 immunohistochemical (IHC) marker as a useful ancillary investigation to differentiate complete hydatidiform mole (CHM) from partial hydatidiform mole (PHM). Materials and Methods: A retrospective study of all histologically diagnosed HM cases over a 20 year period was undertaken. Clinicopathological parameters were extracted from the surgical day book and medical record archives. Archival haematoxylin‑.and eosin‑stained slides and formalin‑fixed paraffin‑embedded tissue blocks of all cases of HM diagnosed within the study period were retrieved and reviewed. Cases of HM were reclassified using the P57kip2 IHC marker. The data obtained were analysed using the SPSS version 23. Results: One hundred cases of HMs were studied. CHM accounted for 68%, while PHM accounted for the remaining 32%. The incidence of HM was 2.98 cases per 1000 deliveries. The ratio of CHM to PHM was found to be 2.1:1. Seventy‑two per cent of the cases were diagnosed in the first trimester, while the remaining 28% were diagnosed in the second trimester of pregnancy. Based on the P57kip2 IHC staining pattern, HM cases were finally reclassified into 68 cases of CHM and 32 cases of PHM. The age range for all the HM cases was 18–50 years with the majority of the cases seen in the third and fourth decades of life. Conclusion: P57kip2 could be useful as an ancillary investigation in confirming the diagnosis of CHM and differentiating it from PHM, particularly in difficult and challenging cases.